Brazilian organic propolis for prevention and treatment of radiation-related oral acute toxicities in head and neck cancer patients: A double-blind randomized clinical trial - Fernandes, Patrícia Maria; Rosalen, Pedro Luiz; Fernandes, Diego Tetzner; Dias-Neto, Emmanuel; Alencar, Severino Matias; Bueno-Silva, Bruno; Alves, Fábio de Abreu; Lopes, Márcio Ajudarte (Frontiers in Pharmacology, 2022)
Background: Oral mucositis (OM) is one of the most important acute toxicities from radiotherapy (RT) in head and neck cancer patients and can impair oncologic treatment. Dysphagia, dysgeusia, pain, and oral candidiasis also, are other common toxicities. Brazilian Organic Propolis (BOP) is a recently described propolis variant and BOP types 4 and 6 have shown important antioxidant, anti-inflammatory, and antifungal properties. Purpose: To investigate the use of BOP as a preventive and/or complementary therapeutic option for radiotherapy-induced oral mucositis, dysphagia, dysgeusia, pain, and oral candidiasis. Additionally, proinflammatory cytokines were assessed to investigate their anti-inflammatory role. Methods: Sixty patients were included in this randomized, double-blind, controlled clinical trial. Patients were randomized to receive either aqueous suspension of a BOP or placebo throughout RT. Also, all patients underwent low-level laser therapy as routine oral care. OM, dysphagia, and dysgeusia were assessed weekly according to WHO and NCI scales. Pain-related to OM was assessed according to a Visual Analog Scale and the presence or absence of oral candidiasis was checked by intraoral examination. Protein levels of TNF-α and IL-1β from oral mucosa were assessed by ELISA. Results: Patients in the propolis group had a lower mean score of OM, dysphagia, dysgeusia, and most patients reported moderate pain. Fewer patients developed oral candidiasis in the propolis group, and the number of episodes was lower among patients that used BOP (p <0.05). In addition, the BOP group presented significantly lower levels of IL-1β since the beginning of treatment when compared with placebo patients (p < 0.05) and a lower level of TNF-α at the end of treatment (p < 0.001). Conclusions: Topic use of BOP reduced TNF-α and IL-1β levels, oral candidiasis episodes, and seems to be a useful complementary option for the prevention and treatment of the main acute oral toxicities of RT. Registration of Clinical Trial: Brazilian Clinical Trials Registry - RBR-9f8c78 (Approved submission in 11/12/2019) https://ensaiosclinicos.gov.br/